Cortical and Subcortical Anatomy of the Parietal Lobe From the Neurosurgical Perspective - Dziedzic, Tomasz Andrzej; Bala, Aleksandra; Marchel, Andrzej (Frontiers in Neurology, 2021)
Introduction: The anatomical structures of the parietal lobe at the cortical and subcortical levels are related mainly to sensory, visuospatial, visual and language function. The aim of this study was to present an intraoperative perspective of these critical structures in terms of the surgical treatment of intra-axial lesions. The study also discusses the results of the technique and the results of direct brain stimulation under awake conditions. Materials and Methods: Five adult brains were prepared according to the Klingler technique. Cortical assessments and all measurements were performed with the naked eye, while white matter dissection was performed with microscopic magnification. Results: Intra-axial lesions within the parietal lobe can be approached through a lateral or superior trajectory. This decision is based on the location of the lesions in relation to the arcuate fascicle/superior longitudinal fascicle (AF/SLF) complex and ventricular system. Regardless of the approach, the functional borders of the resection are defined by the postcentral gyrus anteriorly and Wernicke's speech area inferiorly. On the subcortical level, active identification of the AF/SLF complex and of the optic radiation within the sagittal stratum should be performed. The intraparietal sulcus (IPS) is a reliable landmark for the AF/SLF complex in ~60% of cases. Conclusion: Knowledge of the cortical and subcortical anatomical and functional borders of the resection is crucial in preoperative planning, prediction of the risk of postoperative deficits, and intraoperative decision making.